2020
DOI: 10.2196/18233
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Human Versus Computer-Based Instructions for Exercise on Physical Activity–Related Health Competence in Patients with Hip Osteoarthritis: Randomized Noninferiority Crossover Trial

Abstract: Background Hip and knee osteoarthritis is ranked as the 11th highest contributor to global disability. Exercise is a core treatment in osteoarthritis. The model for physical activity–related health competence describes possibilities to empower patients to perform physical exercises in the best possible health-promoting manner while taking into account their own physical condition. Face-to-face supervision is the gold standard for exercise guidance. Objective … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 51 publications
(60 reference statements)
0
16
0
1
Order By: Relevance
“…The PAHCO model with its multidimensional and integrative view has recently been used in different target groups and settings attributable to both prevention (12,(14)(15)(16)(17)(18)(19) and rehabilitation (12,(20)(21)(22)(23). However, when reviewing the first conceptualtheoretical articles, it becomes obvious that environmental factors hardly play any role within this competence approach (11,24).…”
Section: Figure 1 |mentioning
confidence: 99%
“…The PAHCO model with its multidimensional and integrative view has recently been used in different target groups and settings attributable to both prevention (12,(14)(15)(16)(17)(18)(19) and rehabilitation (12,(20)(21)(22)(23). However, when reviewing the first conceptualtheoretical articles, it becomes obvious that environmental factors hardly play any role within this competence approach (11,24).…”
Section: Figure 1 |mentioning
confidence: 99%
“…We expected that the structured and combined exercise of aerobic and resistance training would improve cardiovascular function and body composition in participants with exercise habits. However, a possible ceiling effect might have prevented further improvements in functioning, even though these participants had completed more scientific exercise [17]. Theresa et al [30] reported that individuals with more "favorable" values at baseline (eg, lower submaximal heart rate) may potentially show a low subsequent training response if a "ceiling effect" limits further improvement in that parameter.…”
Section: Discussionmentioning
confidence: 99%
“…The situation for older people may be worse as a result of complex physical conditions [16]. Older individuals may struggle to exercise because of pain or other symptoms [17].…”
Section: Introductionmentioning
confidence: 99%
“…In den vergangenen Jahren hat die Kompetenzorientierung im Gesundheitssport auf der Basis des BGK-Modells zunehmend an Bedeutung gewonnen. So widmen sich aktuelle Vorhaben und Projekte in der Forschung beispielsweise der kompetenzorientierten Bewegungsförderung von Schülerinnen und Schülern [24,25], Auszubildenden [26,27], Menschen mit chronisch obstruktiver Lungenerkrankung [28,29], Kriegsüberlebenden [30], Personen mit Arthrose [31], Akteurinnen und Akteuren im Bereich Pflege [32], Menschen mit sogenannter geistiger Behinderung [33,34] oder Personen mit Multipler Sklerose [35]. Auch einzelne theoretische Annahmen der BGK wurden konzeptionell weiterentwickelt oder empirisch untermauert [22, 36 -38].…”
Section: Bewegungsbezogene Gesundheitskompetenz (Bgk)unclassified